The Interplay of Soft Skills, Digital Literacy, and Self-Efficacy in Shaping Work Readiness: A Structural Equation Modeling Study of Vocational High School Students - Anas Arfandi; Musdalifah Musdalifah; Sudjani Sudjani; Abdul Haris Setiawan (International Journal of Environment, Engineering and Education, 2026)
Work readiness in vocational education is increasingly shaped by transferable competencies and students’ confidence in applying them in technology-rich workplaces. Although soft skills and digital literacy are widely promoted, evidence remains limited in Indonesian VET contexts regarding how these competencies translate into work readiness through self-efficacy. This study tested a structural mediation model in which soft skills and digital literacy predict work readiness both directly and indirectly via self-efficacy among vocational students who participated in MOOC-based upskilling. A cross-sectional survey was administered to 225 students from the Construction and Housing Engineering program across 22 vocational high schools in 16 districts/cities in South Sulawesi, Indonesia. All constructs were measured using five-point Likert scales, and covariance-based SEM was estimated in AMOS using Maximum Likelihood. The model demonstrated excellent fit (CMIN/DF=1.248, RMSEA=0.001, SRMR=0.005, GFI=0.921, CFI=0.996, TLI=0.989, PNFI=0.762). Soft skills positively predicted self-efficacy (β=0.574; p<0.001) and work readiness (β=0.652, p<0.05), while digital literacy also predicted self-efficacy (β=0.274, p<0.05) and work readiness (β = 0.663, p<0.001). Self-efficacy exhibited the strongest direct effect on work readiness (β=0.778, p<0.05) and partially mediated the effects of soft skills (indirect β=0.447, p<0.05) and digital literacy (indirect β=0.213, p<0.001). Overall, these findings propose an integrated competency–belief model for Indonesian vocational students in a MOOC participation context, highlighting self-efficacy as a key mechanism through which competencies contribute to work readiness. This contribution extends SEM-based evidence on vocational competency development by underscoring the importance of confidence-building alongside skills and digital capability training.